Determination of the Relative Sediment Concentration in Water Bodies Using Remote Sensing Methodology (2017)
Studies for the determination of the relative concentration of sediments (RCS) in bodies of water such as rivers, marshes and river deltas require specialized equipment, field work and laboratory analyses of samples, all with high economic costs. Remote sensing, in regions of the optical electromagnetic spectrum, particularly in the visible range between 0.4 and 0.6 µm, shows radiometric contrasts associated with the relative concentration of sediments in water bodies. This work presents an analysis of the principal spectral, spatial and radiometric properties or characteristics of remote sensors for the determination of the relative concentration of sediments in bodies of water, a methodological process for its cartography at a given time or an established period of time. This cartography is based on digital processing of images rather than direct measurements in the field. Lastly, applications are presented for the delta coast of the southwestern area of the Colombian Caribbean between Barranquilla and Punta Piedra and in the lacustrine area of the Guajaro Reservoir and the Jobo and Capote Wetlands in the upper Canal del Dique, Colombia.